Exploring the relationship Between Cognitive Distortions and Cognitive Failure in College Students: Cognitive distortions and Cognitive failures - Mohamed Abdelrheem, Tarik (Psychology Hub, 2025)
This study aims to investigate the relationship between cognitive distortions and cognitive failures among college students. The primary objective is to examine the direct relationship between cognitive distortions and cognitive failures among college students. Additionally, the study seeks to explore the predictive power of cognitive distortion sub-components in relation to cognitive failure and its components. Furthermore, the study aims to examine whether there are differences in cognitive distortions and failures based on sex and major. Data were collected from a sample of 486 college students, including 240 males. The findings reveal a direct effect between cognitive distortions and cognitive failures, as illustrated by SEM. Some of the factors related to cognitive distortions significantly contribute to predicting cognitive failure components and the total score. Moreover, differences in cognitive failures were observed based on students' majors. In conclusion, this study demonstrates a strong correlation between cognitive distortions and cognitive failures, with cognitive distortions directly affecting cognitive failures. These findings highlight the significance of addressing cognitive distortions in academic settings, with customized treatments potentially offering ways to reduce cognitive errors and enhance students' overall cognitive performance.